2019
DOI: 10.1039/c9sc00323a
|View full text |Cite
|
Sign up to set email alerts
|

Secondary amines as coupling partners in direct catalytic asymmetric reductive amination

Abstract: Direct asymmetric reductive amination utilizing secondary amines as an efficient tool for one-step construction of tertiary chiral amines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 55 publications
1
27
0
Order By: Relevance
“…Establishment of feasibility. In our previous direct asymmetric reductive amination research, iridium catalyst demonstrated prominent reactivity toward imine reduction [43][44][45] . So [Ir(cod)Cl] 2 precursor along with (R)-Segphos was initially evaluated in the reaction of α,β-unsaturated aldehyde 1a and aniline 2a.…”
Section: Resultsmentioning
confidence: 94%
“…Establishment of feasibility. In our previous direct asymmetric reductive amination research, iridium catalyst demonstrated prominent reactivity toward imine reduction [43][44][45] . So [Ir(cod)Cl] 2 precursor along with (R)-Segphos was initially evaluated in the reaction of α,β-unsaturated aldehyde 1a and aniline 2a.…”
Section: Resultsmentioning
confidence: 94%
“…Primary amines including anilines, [2a, 8] benzylamine, [9] hydrazines, [10] and hydrazides [8e, 11] have been utilized as the organic amine sources to form the corresponding secondary chiral amines (Scheme 1 a II). Very recently, and with the help of multiple additives, secondary amines were effectively employed as N sources in direct ARA to afford tertiary chiral amines (Scheme 1 a II) [12] . The conditions adopted for the reactions of inorganic nitrogen sources are significantly different from those used for organic nitrogen sources, and typically feature high reaction temperatures, protic solvents, and ruthenium‐diphosphine catalysts.…”
Section: Methodsmentioning
confidence: 99%
“…The desired product 3 a was obtained with the best steric selectivity and yield when L5 e was used. The chiral phosphoramidite ligand L5 b was previously applied in ARA reactions of acetophenones with dialkylamines to form chiral tertiary amines under basic conditions [12] . In comparison, the stereoselective formation of the much smaller intermediate product 2 a required a higher level of confinement [17] .…”
Section: Methodsmentioning
confidence: 99%
“…Chang and co-workers developed a highly efficient and novel approach to tertiary chiral amines via direct catalytic asymmetric reductive amination. 24 In this protocol, secondary amines undergo direct reductive amination with ketones catalysed by Ir-phosphoramidite ligand complexes. Rivastigmine, which is used in the treatment of Alzheimer's and Parkinson's type diseases, was synthesised by this facile and scalable method ( Fig.…”
Section: Organic Chemistry Frontiers Reviewmentioning
confidence: 99%